2008
DOI: 10.1063/1.2998597
|View full text |Cite
|
Sign up to set email alerts
|

Effective polarization fatigue from repeated dielectric barrier discharges in cellular polypropylene ferroelectrets

Abstract: Polarization fatigue is observed when cellular polypropylene (PP) ferroelectrets are subjected to high-voltage cycles. The fatigue rate strongly depends on the amplitude and the number of the applied voltage cycles, whereas the frequency and the waveform of the voltage do not have a strong influence. The much lower piezoelectric activity of significantly fatigued cellular PP ferroelectret films recovers in part after a storage period of typically several hours in ambient air. It is believed that the effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…It is observed that for severely fatigued samples, the piezoelectricity partially recovers with the storage time after fatiguing [10]. Right after the fatigue process with 1.8×10 5 DBD cycles, a much lower d 33 coefficient of around 15% of the initial value is observed.…”
Section: B Partial Recovery and The Stability Of The Piezoelectricitmentioning
confidence: 80%
See 1 more Smart Citation
“…It is observed that for severely fatigued samples, the piezoelectricity partially recovers with the storage time after fatiguing [10]. Right after the fatigue process with 1.8×10 5 DBD cycles, a much lower d 33 coefficient of around 15% of the initial value is observed.…”
Section: B Partial Recovery and The Stability Of The Piezoelectricitmentioning
confidence: 80%
“…When fatigued samples are stored in the lab for sufficiently long periods, the chargeability of the cavities partially recovers. However, repeated DBDs are detrimental to the stability of the internally trapped charges and hence of the piezoelectricity [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…Our previous study showed that repeated DBDs in air result in significant deterioration of the chargeability of the voids, leading to fatigue in the piezoelectricity in ferroelectrets. 27 In this paper, we present new experimental results to confirm and further illustrate the plasma-polymer interactions during repeated DBDs in the voids as the mechanism of polarization fatigue. We show that the repeated microplasma discharges modify the internal polymer surfaces of cellular ferroelectrets and thus facilitate the charging process, but they also deteriorate the chargeability of the voids, as well as the stability of the piezoelectricity in the cellular polymer, which demonstrates the influence of molecular dynamics and physico-chemical processes.…”
mentioning
confidence: 70%
“…Self-healing of the DBD-induced damage over time: Partial recovery of the piezoelectricity Partial recovery of the piezoelectricity in significantly fatigued cellular PP ferroelectrets had already been observed in our previous study and was attributed to the loss of polar low-molecular-weight oxidized material from the internal surfaces of the voids. 27 Figure 1 shows the evolution of the piezoelectric d 33 coefficients as a function of storage time in ambient laboratory conditions for cellular PP films subjected to slight and moderate fatigue. For comparison, the results for one severely fatigued sample are also shown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation